COMPUTATIONAL DFT ANALYSIS OF MONOCARBONYL CURCUMIN AND PYRAZOLE DERIVATIVES: MOLECULAR GEOMETRY, ELECTROSTATIC SURFACE POTENTIAL, ELECTRONIC TRANSITION SPECTRA, AND MULLIKEN CHARGES - Hayder S. Mahdi; Tahseen A. Alsalim (International Journal Multidisciplinary (IJMI), 2026)
Objective: Monocarbonyl curcumin (MCC) analogues and those of pyrazole derivatives were investigated in their structural and electronic features. Method: Applying the Density Functional Theory (DFT) at B3LYP/6-311G++(d,p) level, it is examined molecular geometry, electrostatic surface potential (ESP), frontier molecular orbitals (FMO), and Mulliken charges. Results: Results show that although MCC compounds have a near-planar structure, the pyrazole derivatives develop non-planar geometries. Electronic absorption spectra, based on TD-DFT, display prominent transitions in UV-visible areas, where compound BPY yielded the lowest transition energy gap (2.8774 eV) and maximum absorption wavelength ($λ_{max}$ = 430.89 nm). Novelty: The results imply the effect of the formation of pyrazole rings on electronic delocalization and charge transfer characteristic and provide knowledge for designing more stable and biologically active curcumin-based heterocyclic systems.